2017
DOI: 10.1111/febs.14270
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of NFU‐1 metallocofactor binding‐site substitutions—impacts on iron–sulfur cluster coordination and protein structure and function

Abstract: Iron-sulfur (Fe/S) clusters are ancient prosthetic groups found in numerous metalloproteins and are conserved across all kingdoms of life due to their diverse, yet essential functional roles. Genetic mutations to a specific subset of mitochondrial Fe/S cluster delivery proteins are broadly categorized as disease-related under multiple mitochondrial dysfunction syndrome (MMDS), with symptoms indicative of a general failure of the metabolic system. Multiple mitochondrial dysfunction syndrome 1 (MMDS1) arises as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…The transfer of Fe–S clusters to apo aconitase from an NFU1 [2Fe-2S] donor was also evaluated by EPR (Figure ). While earlier work had suggested NFU1 to bind a [4Fe-4S] cluster, both recent biochemical studies , and the EPR signature shown in Figure A are all consistent with the [2Fe-2S] form of NFU1 as the active protein in cluster trafficking and delivery. The g values observed following transfer of the [2Fe-2S] clusters indicate the possible presence of a [3Fe-4S] cluster, which has been previously observed in the isolation of aconitase based on the g value of 2.01 and forms because of oxidation of the bound [4Fe-4S] cluster .…”
Section: Resultssupporting
confidence: 60%
“…The transfer of Fe–S clusters to apo aconitase from an NFU1 [2Fe-2S] donor was also evaluated by EPR (Figure ). While earlier work had suggested NFU1 to bind a [4Fe-4S] cluster, both recent biochemical studies , and the EPR signature shown in Figure A are all consistent with the [2Fe-2S] form of NFU1 as the active protein in cluster trafficking and delivery. The g values observed following transfer of the [2Fe-2S] clusters indicate the possible presence of a [3Fe-4S] cluster, which has been previously observed in the isolation of aconitase based on the g value of 2.01 and forms because of oxidation of the bound [4Fe-4S] cluster .…”
Section: Resultssupporting
confidence: 60%
“…Moreover, Mössbauer and NMR studies have also demonstrated that reconstituted human NFU1 exclusively contains a [4Fe-4S] 2+ cluster ( 53 , 54 ). This reinterpretation necessitates a major reevaluation of the results and conclusions made by Cowan and co-workers ( 55 , 56 , 57 , 58 , 59 ) about human NFU1. The discovery that both NFU4 and NFU5 are [4Fe-4S] 2+ cluster-binding proteins, coupled with our inability to assemble a [2Fe-2S] 2+ cluster on NFU4 and NFU5 either by reconstitution or cluster transfer from [2Fe-2S]-ISCA1a/2 or [2Fe-2S]-GRXS15, is in accord with the statement that all mitochondrial NFU proteins function in [4Fe-4S] 2+ cluster trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the human and yeast mitochondrial NFU proteins are part of the ISC machinery and have been proposed to function exclusively as [4Fe-4S] 21 cluster-carrier proteins based on both in vivo and in vitro evidence (33)(34)(35)(52)(53)(54). This hypothesis has recently been challenged in a series of five publications by Cowan and co-workers (55)(56)(57)(58)(59), which claim that human mitochondrial NFU1 is a [2Fe-2S] 21 cluster-carrier protein, based on UV-visible absorption/CD and EPR data. This interpretation is incorrect, based on our characterization of the homologous mitochondrial At NFU4 and NFU5 as [4Fe-4S] 21 cluster-carrier proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro data from James Cowan's group (The Ohio State University) has shown that at least two of these variations affect NFU1 dimerization rather than ISC binding itself. They have performed detailed analyses of both the NFU1 Gly189Arg (nfu-1 Gly147Arg) and Gly208Cys (nfu-1 Gly166Cys) variants and found that the Gly189Arg variant biases NFU1 toward a monomeric state whereas the Gly208Cys variation biases NFU1 toward dimerization, preventing release of ISCs to the recipient ISPs (Fig 7) [82][83][84]. Therefore, ISC binding and release are affected in both the Gly147Arg and Gly166Cys mutants, but it is a secondary effect to NFU-1 dimerization.…”
Section: Nfu-1 Mutations and Impaired Isc Handlingmentioning
confidence: 99%
“…NFU1/NFU-1 coordinates ISCs as a dimer, and it is believed to typically function as a homodimer although other binding partners are known [8]. Assuming that NFU-1 is functioning as a homodimer, the Gly147Arg mutant is more likely to expose an ISC to the environment because of the fact that this mutation biases NFU1/NFU-1 to the monomeric state [82,84]. If the ISC coordinated by this mutant is exposed to the environment, it can react with H 2 O 2 via Fenton chemistry or with O 2 via redox mechanisms.…”
Section: Oxidative Stress and Iron Dysregulationmentioning
confidence: 99%